Pengembangan Buku Ajar Mata Kuliah Senam Lantai bagi Mahasiswa Program Studi Pendidikan Jasmani - Citra Azhariat Malasari; Azizil Fikri (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2021)
The purpose of this study was to develop a textbook for floor gymnastics courses for students of the Physical Education Study Program, University of Muhammadiyah Kotabumi. This research method uses the Borg and Gall development procedure which consists of 10 steps. However, in this development research, the research did not use all of it but only with 7 steps, namely, 1) needs analysis, 2) product manufacture, 3) product validation, 4) small group trial, 5) product revision phase I, 6) group trial. large 7) product revision phase II. The results of this study are the results of material expert validation with an overall average validation result of 87.85%, the results of media and design expert validation with a minimum score of 27, a maximum score of 108, a score of 97 results with a percentage of 89.81%, Results of the Trial Stage Assessment I (small group) with a percentage result of 91.11%, Phase II Assessment Results (large group) with a percentage result of 81.08%. In conclusion, the development of floor exercise textbooks can already be used in floor gymnastics courses Keywords: Textbooks, Floor gymnastics